Implementation of Jean Piaget's Cognitive Development Theory in Science Learning in Elementary Schools and Its Relevance to SDGs 4 - Isna Qurrotun Aini; Rafii Fathul Alim; Yusuf Firmansyah (Journal on Smart Learning Technologies, 2025)
Quality education (SDGs 4) demands a paradigm shift from passive learning to active knowledge construction, particularly at the Elementary School (SD) level as the foundation for scientific literacy. In reality, Science (IPA) learning in elementary schools is still dominated by abstract lecture methods, which conflict with the cognitive needs of students, the majority of whom are in the concrete operational stage (ages 7–11). This study aims to analyze and synthesize the practical implementation of Jean Piaget's cognitive development theory in elementary school science learning and its relevance in supporting the achievement of SDGs 4 targets. The research employs a literature review method with a descriptive-analytical approach, examining various scientific studies related to the application of Piaget's constructivist principles within the science context. The synthesis results identify three pillars of effective implementation: 1) The Shift in the Teacher's Role, which involves the teacher transitioning into a facilitator who designs cognitive disequilibrium; 2) The Centrality of Concrete Media, which mandates the use of hands-on media (traditional and digital, such as interactive simulations) to bridge abstract concepts into observable (concrete) thinking; and 3) Relevant Learning Models, specifically the application of constructivist models like Inquiry-Based Learning and Discovery Learning that directly train students' logical skills. The conclusion indicates that science learning aligned with the concrete operational principles significantly improves students' concept comprehension, critical thinking skills, and scientific literacy, which are central to achieving Quality Education targets (SDGs 4.1 and 4.7). Therefore, a mandatory transition from textbook-centered instruction to activity-centered instruction in elementary schools is recommended.